The Relationship Between Self-Compassion and Blood Pressure Control Behaviour in Patients with Hypertension - Br Munthe, Cristina Lasmaria; Aziz, Ari Rahmat; Nopriadi, Nopriadi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
Blood pressure control behavior by hypertensive patients is driven by various factors, one of which is an attitude that encourages positive behavior. Self-compassion is an attitude of compassion for oneself towards problems and diseases suffered by caring, understanding and giving kindness to oneself. Objective: This study aims to determine the relationship between self-compassion and blood pressure control behavior in hypertensive. Methods: This research is a quantitative research with descriptive correlation design and cross sectional approach. The instruments used for data collection in this study were self-compassion scale questionnaire and blood pressure control behavior questionnaire. The research sample was 144 respondents selected by purposive sampling technique. The analysis used was the chi-square test. Results: The results of bivariate analysis using chi-square obtained the results of p-value (0.001) < alpha (0.05). Conclusion: There is a significant relationship between self-compassion and blood pressure control behavior in hypertensive patients at Rejosari Health Center Pekanbaru. The correlation obtained is positive, meaning that the higher the self-compassion, the better the blood pressure control behavior and vice versa, the lower the self-compassion, the less good the blood pressure control behavior.